Career Interest for Students with Special Needs: A Systematic Review - Zakaria, Zuraini; Alias , Aliza; Ali, Manisah Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This systematic review is focused of career interest for the students with special needs that based on previous studies conducted with the collection of several empirical studies from 2010 to 2018. This study used three main data sources which are E-Journal UKM online, Google Scholar and ScienceDirect that based on search using keywords Career Interest, Career Theories, Career Models, Special Needs Students and Person with Disabilities. A total of 20 journal articles were identified to answer the questions and objectives of the study. This study consists of students with special needs in various categories including learning disabilities, physical disabilities, visibility and hearing impaired. This study aims to identify strategies to nurture career interest in special needs students as well as to research the theory and model of career selection used to support special needs students’ career development. The findings showed that parents’ involvement and teachers’ support are the most influenced special needs students’ career interest compared to other factors. The findings showed that there were several theories and models used to support the special needs students’ career development which are Holland’s Theory of Personalities and Environment (1997), Super’s Theory (1990), Krumboltz’s Theory (1996), Social Cognitive Career Theory (1994) and Self-Efficacy Theory of Bandura (1986). One of the implications in this study is expected to help students with special needs, parents and teachers in fostering career interest in line with their capacities and capabilities that have been identified.